Co-creating Ethical Space in wildlife conservation: a case study of moose (Mooz; Alces alces) research and monitoring in the Robinson Huron Treaty region (Ontario, Canada) - Kathryn Yarchuk; Joseph Northrup; Allyson Menzies; Nadine Perron; Claire Kemp; Samantha Noganosh; Jesse Popp (Canadian Science Publishing, 2024)
The strengths of Indigenous Knowledges and need for reconciliation are increasingly recognized within conservation, leading to a rise in collaborative, cross-cultural research initiatives. As both a cultural keystone and important harvest species, moose are of value to both Indigenous and non-Indigenous Peoples, presenting an opportunity to pursue moose monitoring strategies that embrace the strengths of Indigenous and Western knowledges. While various frameworks provide theoretical direction on how to do so, few resources outline how to apply them in practice. Leaning on guidance of the Ethical Space framework, we explored the meaning and application of value-based approaches in the context of moose monitoring in central Ontario through semi-structured interviews with First Nation communities, the Ontario provincial crown government, and academic researchers. Collectively, 20 core values were identified to be important when bringing Indigenous and non-Indigenous partners together, coupled with a range of tangible actions necessary for fostering Ethical Space. Values and actions reflected three main themes: an emphasis on the long term, the importance of building and maintaining relationships, and the ability to evolve and adapt over time. Insights from this research provide tools and guidance for others interested in enacting Ethical Space in the context of cross-cultural wildlife monitoring and research.